2018
DOI: 10.1002/ldr.2873
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of land‐use change effects on runoff and soil erosion of a hilly basin — the Yanhe River in the Chinese Loess Plateau

Abstract: Starting in 1999, the Grain‐for‐Green Programme has been implemented in the Loess Plateau to alleviate the severe soil erosion by converting steeply sloping croplands to forestlands or grasslands. To quantify the effects of these conservation efforts, this study identified the land‐use changes between 2000 and 2015 and quantified their impacts on runoff and erosion using the Soil and Water Assessment Tools (SWAT) and a typical hilly basin, the Yanhe River basin as a case‐study. To heighten the applicability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 41 publications
5
43
3
Order By: Relevance
“…When this parameter was involved, R 2 , NS, and RSR were improved to 0.85, 0.83, and 0.41 for calibration and 0.89, 0.88, and 0.34 for validation, respectively (Table 4). Our sensitivity analysis results showed that SOL_BD was the most sensitive parameter, a finding that differs from the previous conclusion that CN2 is the most sensitive parameter for streamflow simulation supported by the long hold infiltration excessive overland flow runoff generation mechanism in the Loess region [3,20,28,51]. Superior performance of SOL_BD was likely caused by a combination of lateral and vertical movement of water in the loess soils, as it was also observed in the Yanhe River Basin of the Loess Plateau [31].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…When this parameter was involved, R 2 , NS, and RSR were improved to 0.85, 0.83, and 0.41 for calibration and 0.89, 0.88, and 0.34 for validation, respectively (Table 4). Our sensitivity analysis results showed that SOL_BD was the most sensitive parameter, a finding that differs from the previous conclusion that CN2 is the most sensitive parameter for streamflow simulation supported by the long hold infiltration excessive overland flow runoff generation mechanism in the Loess region [3,20,28,51]. Superior performance of SOL_BD was likely caused by a combination of lateral and vertical movement of water in the loess soils, as it was also observed in the Yanhe River Basin of the Loess Plateau [31].…”
Section: Discussioncontrasting
confidence: 99%
“…Twenty-four input parameters for running SWAT model were selected for sensitivity analysis according to the literature review from watersheds with similar characteristic to Xinshui watershed of the Loess Plateau (Table 1) [10,20,28,30,35].…”
Section: Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, most researchers focus on the contributions of the whole underlying surface to run‐off reduction; thus, the contributions of every soil and water conservation measure to run‐off reduction remain uncertain (Gao et al, ; Gu, Mu, Gao, Zhao, & Sun, ; Li et al, ; Liang et al, ). Certain studies have evaluated the hydrological responses to only one measure, such as reservoir construction or land use change caused by vegetation restoration, in only one watershed (Li, Liang, Bao, Wang, & Hu, ; Yang et al, ; Yang & Lu, ). More evidence is needed to better understand how each measure and climate change impact run‐off.…”
Section: Introductionmentioning
confidence: 99%
“…The dam at Nkula Falls that supplies water into the power station has, in recent times, been threatened with massive siltation, some studies attributing this to increased human population and agricultural activities [5,6,8]. The conceptual setting of this study originates from a strong link that exists between land use change and soil erosion [8,[11][12][13][14][15]. Land use and management practices are important factors in determining the extent of soil erosion [8,15].…”
Section: Introductionmentioning
confidence: 99%